2011
DOI: 10.1039/c1lc20328b
|View full text |Cite
|
Sign up to set email alerts
|

Photoreversible fragmentation of a liquid interface for micro-droplet generation by light actuation

Abstract: We describe a method to induce by light a reversible switch from a continuous two-phase laminar flow to a droplet generating regime, in microfluidic devices with a usual water-in-oil flow focusing geometry. It consists in adding a photosensitive surfactant to the aqueous phase to modulate using light the interfacial energy between flowing liquids and the microfluidic substrate. We show that UV irradiation induces liquid fragmentation into monodisperse water microdroplets and that many cycles of reversible and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 35 publications
(16 reference statements)
0
48
0
Order By: Relevance
“…49 The system is reversible, and cis -AzoTAB isomerizes back to trans configuration upon blue light (475 nm) illumination (Figure 1A). AzoTAB has been mainly used for the photocontrol of surface tension, 50,51 DNA conformation, 49,52,53 and gene expression systems. 5456 Here, we investigated how light affected the behavior of lipid GUVs in the presence of AzoTAB.…”
Section: Resultsmentioning
confidence: 99%
“…49 The system is reversible, and cis -AzoTAB isomerizes back to trans configuration upon blue light (475 nm) illumination (Figure 1A). AzoTAB has been mainly used for the photocontrol of surface tension, 50,51 DNA conformation, 49,52,53 and gene expression systems. 5456 Here, we investigated how light affected the behavior of lipid GUVs in the presence of AzoTAB.…”
Section: Resultsmentioning
confidence: 99%
“…When the light source was removed, the flow returned to laminar. This was a reversible process and the flow was successfully switched multiple times in the same experiment [125]. A recent study by Toyota et al [127] demonstrated an autonomous droplet which spontaneously moved once placed in an aqueous solution in which "fuel" surfactant had been dispersed.…”
Section: Figure 18 Photo-induced Confirmation Change Of Azotab Betwementioning
confidence: 96%
“…Recently it was demonstrated that the AzoTAB surfactant could be used to change the flow in a microfluidic system from laminar to segmented flow (droplets) [125]. Initially the system had a two-phase flow, one flow was aqueous (which contained the AzoTAB surfactant) and the second was an oil phase.…”
Section: Figure 18 Photo-induced Confirmation Change Of Azotab Betwementioning
confidence: 99%
“…In the large majority of cases, the drop motion is induced by an interfacial energy gradient at a solid/liquid interface (wettability gradient) and/or at a free interface (Marangoni stress) 3. This has resulted in a plethora of studies to elucidate the fundamental mechanisms that convert such gradients into drop motion4 as well as to develop strategies to manipulate drops under the control of various external signals, such as thermal,5 electrical2, 6, 7 and optical8, 9, 10, 11, 12, 13 stimuli. Most of these approaches necessitate the implementation of rather complex components, such as electrodes or optical elements, or the development of systems that are intrinsically responsive to the desired stimulus, such as photo‐ or thermosensitive substrates 8, 9.…”
mentioning
confidence: 99%